2021
DOI: 10.1186/s12870-021-03220-1
|View full text |Cite
|
Sign up to set email alerts
|

PbLAC4-like, activated by PbMYB26, related to the degradation of anthocyanin during color fading in pear

Abstract: Background Decrease in anthocyanin content results in the loss of red color in leaves, petals and receptacles during development. The content of anthocyanin was affected by the biosynthesis and degradation of anthocyanin. Compared with the known detailed mechanism of anthocyanin biosynthesis, the degradation mechanism is not fully investigated. It is vital to study the degradation mechanism of anthocyanin in pear for promoting the accumulation of anthocyanin and inhibiting the red fading in pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Our results showed that the mutant phenotypes of the tt19 mutant could be partly restored by the expression of RsGSTF12. Like the functions of MdGSTF6 and GhGSTF12, RsGSTF12 could complement anthocyanin pigmentation in vegetative tissues, despite no color change evident in the seed coat (Figure 6) (Jiang et al, 2019;Zhao et al, 2021). Overall, RsGSTF12 is involved in the process of anthocyanin accumulation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our results showed that the mutant phenotypes of the tt19 mutant could be partly restored by the expression of RsGSTF12. Like the functions of MdGSTF6 and GhGSTF12, RsGSTF12 could complement anthocyanin pigmentation in vegetative tissues, despite no color change evident in the seed coat (Figure 6) (Jiang et al, 2019;Zhao et al, 2021). Overall, RsGSTF12 is involved in the process of anthocyanin accumulation.…”
Section: Discussionmentioning
confidence: 92%
“…The transient expression system is a direct and important methodological tool used to understand the functions of proteins and is now widely used in various plants, such as apple, pear, and strawberry ( Jiang et al, 2019 ; Castillejo et al, 2020 ; Zhao et al, 2021 ). In this study, when RsGSTF12 and GmMYB75 (a positive anthocyanin regulator in soybean) were co-transferred transiently into radish leaves, the leaves appeared much more anthocyanin compared with either of them injected ( Figure 5A ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some transcription factors can even regulate the appearance of the white phenotype in plant tissues. For example, PbMYB26 can degrade anthocyanin in the petals, leaves, and pedicels of pear by activating the expression of PbLAC4 , and even produce a white phenotype [ 41 ]. In tobacco, CRISPR/Cas9-induced mutation in the RcMYB3 gene of Rubus chingii Hu.…”
Section: Discussionmentioning
confidence: 99%
“…However, the modulation of anthocyanin degradation has not been fully investigated. In pear, PbLAC4-like gene functions to regulate anthocyanin degradation through activation of PbMYB26 during fading [ 65 ]. A study of Malus hupehensis petals fading from red to white found significantly higher expression levels of PAL , CHS , CHI , DFR , FLS , ANS , UFGT , MYB10 , and MYB12 at early development stages than later stages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is only single cell layer in Papaver somniferum L., while there are several cell Similarly, co-expression analysis was conducted between phytohormone content and corresponding genes based on the correlation coefficient and significance level. The results show that JA, ACC, ABA, GA3, indol-3-acetic acid, indole-3-carboxaldehyde, isopentenyl adenosine, kinetin, melatonin, methyl indole-3-acetate, methyl jasmonate, SA, and transzeatin-riboside had 73, 104, 74, 4,39,65,63,61,29,63,35,118, and 69 pairs, respectively (Figure 9b).…”
Section: Effect Of Morphological Changes Of Petal Color On Petal Colo...mentioning
confidence: 99%